Nuclear Factor κB is Required for Tumor Growth Inhibition Mediated by Enavatuzumab (PDL192), a Humanized Monoclonal Antibody to TweakR - Purcell, James W.; Kim, Han K.; Tanlimco, Sonia G.; Doan, Minhtam; Fox, Melvin; Lambert, Peter; Chao, Debra T.; Sho, Mien; Wilson, Keith E.; Starling, Gary C.; Culp, Patricia A. (Frontiers in Immunology, 2014)
TweakR is a TNF receptor family member, whose natural ligand is the multifunctional cytokine TWEAK. The growth inhibitory activity observed following TweakR stimulation in certain cancer cell lines and the overexpression of TweakR in many solid tumor types led to the development of enavatuzumab (PDL192), a humanized IgG1 monoclonal antibody to TweakR. The purpose of this study was to determine the mechanism of action of enavatuzumab’s tumor growth inhibition and to provide insight into the biology behind TweakR as a cancer therapeutic target. A panel of 105 cancer lines was treated with enavatuzumab in vitro; and 29 cell lines of varying solid tumor backgrounds had >25% growth inhibition in response to the antibody. Treatment of sensitive cell lines with enavatuzumab resulted in the in vitro and in vivo (xenograft) activation of both classical (p50, p65) and non-classical (p52, RelB) NFκB pathways. Using NFκB DNA binding functional ELISAs and microarray analysis, we observed increased activation of NFκB subunits and NFκB-regulated genes in sensitive cells over that observed in resistant cell lines. Inhibiting NFκB subunits (p50, p65, RelB, p52) and upstream kinases (IKK1, IKK2) with siRNA and chemical inhibitors consistently blocked enavatuzumab’s activity. Furthermore, enavatuzumab treatment resulted in NFκB-dependent reduction in cell division as seen by the activation of the cell cycle inhibitor p21 both in vitro and in vivo. The finding that NFκB drives the growth inhibitory activity of enavatuzumab suggests that targeting TweakR with enavatuzumab may represent a novel cancer treatment strategy.